A Cross-Cultural Study of Worker Attitudes in a Bicultural Economic Environment - Kothari, Vinay (Relations industrielles / Industrial Relations, 1973)
This research study examines the attitudes of French and English workers of New Brunswick, and it attempts to show similarities and differences in the attitudes of the two cultural groups. Specifically, the worker's attitudes towards his co-workers, economic benefits, administrative practices, physical conditions, and the work itself are examined and analyzed. Overall, the study points out that there are no significant differences between the attitudes of French and those of English. But the differences are likely to increase in the years to come because of social trends.